A TABLE FOR ALL: Eucharist as Model for Radical Welcome and Community - Shea Watts (Scriptura Indonesia, 2022)
This article considers the Eucharist as a framework for communal life. Rather than a place of privilege or exclusion, the table creates an inclusive vision for how the world should be. It is a ritual of imagination and transformation, reaching beyond the symbolic table into a material world of need. Drawing on the work of Clàudio Carvalhaes, as well as the Eucharistic instructions of Jesus and practices of the early church, I explore the political and communal contours of participating in the holy meal. In this way, Eucharist provides nourishment and sustenance for the work of justice in the world.